Enhancement of Ethanol Vapor Sensing Properties of ZnO Nanoplates by Simple Composition with α-Fe₂O₃ Nanorods - Do, Duc Tho; Luong, Huu Phuoc; Nguyen, Duy Thanh; Nguyen, Dinh Thieu; Vu, Xuan Hien; Dang, Duc Vuong; Nguyen, Duc Chien (Old Journal, 2017)
ZnO nanoplates with average size of and nanorods with an average diameter and a length of 50 nm and several μm have been prepared through hydrothermal treatment method. Both materials were mixed in weight ratios () of 1/9, 2/8, 3/7, 1/1, 7/3, 8/2 and 9/1 to produce nanocomposite materials. Ethanol vapor properties of films derived from obtained materials, pristine nanoplates ZnO and pristine nanorods were investigated at temperatures in the range of and ethanol vapor concentrations in the range of 125–1500 ppm. The result shows that the material of 80 wt.% ZnO/20 wt.% exhibits the highest response to ethanol vapor at . The improvement in the ethanol vapor sensing characteristics of this material compared with pristine nanoplates ZnO and pristine nanorods is attributed to the formation of heterojunctions in materials and their porous structure.